Site-Specific Variations in Bone Mineral Density under Systemic Conditions Inducing Osteoporosis in Minipigs - Schulz, Matthias C.; Kowald, Jan; Estenfelder, Sven; Jung, Roland; Kuhlisch, Eberhard; Eckelt, Uwe; Mai, Ronald; Hofbauer, Lorenz C.; Stroszczynski, Christian; Stadlinger, Bernd (Frontiers in Physiology, 2017)
Osteoporosis is a systemic bone disease with an increasing prevalence in the elderly population. There is conflicting opinion about whether osteoporosis affects the alveolar bone of the jaws and whether it poses a risk to the osseointegration of dental implants. The aim of the present study was to evaluate the effects of systemic glucocorticoid administration on the jaw bone density of minipigs. Thirty-seven adult female minipigs were randomly divided into two groups. Quantitative computed tomography was used to assess bone mineral density of the lumbar spine as well as the mandible and maxilla, and blood was drawn. One group of minipigs initially received 1.0 mg prednisolone per kg body weight daily for two months. The dose was tapered to 0.5 mg per kg body weight per day thereafter. The animals in the other group served as controls and received placebo. Quantitative computed tomography and blood analysis were repeated after six and nine months. Bone mineral density (BMD) was compared between the two groups by measuring Hounsfield units, and serum levels of several bone metabolic markers were also assessed. A decrease in BMD was observed in the jaws from baseline to nine months. This was more pronounced in the prednisolone group. Statistically significant differences were reached for the mandible (p<0.001) and the maxilla (p<0.001). The administration of glucocorticoids reduced the bone mineral density in the jaws of minipigs. The described model shows promise in the evaluation of osseointegration of dental implants in bone that is compromised by osteoporosis.